Cigarette smoke stimulates clonal expansion of Jak2V617F and Tet2-/- cells - Ramanathan, Gajalakshmi; Chen, Jane H.; Mehrotra, Nitya; Trieu, Tiffany; Huang, Aaron; Mas, Eduard; Monterrosa Mena, Jessica E.; Bliss, Bishop; Herman, David A.; Kleinman, Michael T.; Fleischman, Angela G. (Frontiers in Oncology, 2023)
Somatic mutations in myeloid growth factor pathway genes, such as JAK2, and genes involved in epigenetic regulation, such as TET2, in hematopoietic stem cells (HSCs) leads to clonal hematopoiesis of indeterminate potential (CHIP) which presents a risk factor for hematologic malignancy and cardiovascular disease. Smoking behavior has been repeatedly associated with the occurrence of CHIP but whether smoking is an environmental inflammatory stressor in promoting clonal expansion has not been investigated. We performed in vivo smoke exposures in both wildtype (WT) mice and transplanted mice carrying Jak2V617F mutant and Tet2 knockout (Tet-/-) cells to determine the impact of cigarette smoke (CS) in the HSC compartment as well as favoring mutant cell expansion. WT mice exposed to smoke displayed increased oxidative stress in long-term HSCs and suppression of the hematopoietic stem and progenitor compartment, but smoke exposure did not translate to impaired hematopoietic reconstitution in primary bone marrow transplants. Gene expression analysis of hematopoietic cells in the bone marrow identified an imbalance between Th17 and Treg immune cells suggesting a local inflammatory environment. We also observed enhanced survival of Jak2V617F cells exposed to CS in vivo and cigarette smoke extract (CSE) in vitro. WT bone marrow hematopoietic cells from WT/Jak2V617F chimeric mice exposed to CS demonstrated an increase in neutrophil abundance and distinct overexpression of bone marrow stromal antigen 2 (Bst2) and retinoic acid early transcript 1 (Raet1) targets. Bst2 and Raet1 are indicative of increased interferon signaling and cellular stress including oxidative stress and DNA damage, respectively. In chimeric mice containing both WT and Tet2-/- cells, we observed an increased percentage of circulating mutant cells in peripheral blood post-cigarette smoke exposure when compared to pre-exposure levels while this difference was absent in air-exposed controls. Altogether, these findings demonstrate that CS results in an inflamed bone marrow environment that provides a selection pressure for existing CHIP mutations such as Jak2V617F and Tet2 loss-of-function.